PENGARUH LIVE STREAMING SHOPPING, PRICE DISCOUNT, DAN SERVICE QUALITY TERHADAP SATISFACTION DENGAN PURCHASE DECISION SEBAGAI VARIABEL INTERVENING PADA USAHA FRAME&CASEBYDITTA DI SITUBONDO - Safara, Andita Veronika; Sari, Lita Permata; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Entrepreneurship is an activity that is full of time sacrifices, and the focus of business activities by an entrepreneur is profit or gain. Business activities carried out by an entrepreneur are activities that require effort and time that are not small. The purpose of this study is to analyze and test the effect of Live streaming shopping, Price discount, and Service quality on Satisfaction through Purchase decision. This research is an explanatory study. The population in this study is part of Frame&casebyditta consumers. The sampling technique is determined by Simple Random Sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS SEM). The results of the direct influence test using the Smart Pls 3.0 Application, show that Live streaming shopping has a positive but insignificant effect on Purchase decision, Price discount has a positive but insignificant effect on Purchase decision, Service quality has a significant positive effect on Purchase decision, Live streaming shopping has a positive but insignificant effect on Satisfaction, Price discount has a negative but insignificant effect on Satisfaction, Service quality has a significant positive effect on Satisfaction, Purchase decision has a significant positive effect on Satisfaction, Live streaming shopping has a positive but insignificant effect on Satisfaction through Purchase decision, Price discount has a positive but insignificant effect on Satisfaction through Purchase Decision, Service quality has a significant positive effect on Satisfaction through Purchase Decision.